2011
DOI: 10.1021/ma200795g
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Non-Covalent Interactions to Modulate the Dispersion of Fullerenes in Polymer Nanocomposites

Abstract: Polymer nanocomposites (PNCs) are materials based on a class of filled plastics that contain relatively small amounts of nanoparticles, which can impart improved structural, mechanical, and thermal properties relative to the neat polymer. However, the homogeneous dispersion of the nanoparticles into a polymer matrix is critical and an impeding factor for the controlled enhancement of PNC properties. In this work, we provide new insight into the importance of polymer chain connectivity and nanoparticle shape an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 27 publications
(60 reference statements)
4
32
3
Order By: Relevance
“…Of relevance to our present work is the recent experimental discovery that improved particle dispersion can be achieved by using chemically heterogeneous, amorphous copolymers. 22 Specifically, AB random copolymers (RCP) of intermediate composition, where the A and B monomers display different wettability with the particle, results in major improvement of the dispersion of fullerenes relative to both the corresponding pure homopolymers. By combining the Polymer Reference Interaction Site Model (PRISM) integral equation theory and computational chemistry input, a predictive understanding of this phenomenon for fullerenes in RCP melts has been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Of relevance to our present work is the recent experimental discovery that improved particle dispersion can be achieved by using chemically heterogeneous, amorphous copolymers. 22 Specifically, AB random copolymers (RCP) of intermediate composition, where the A and B monomers display different wettability with the particle, results in major improvement of the dispersion of fullerenes relative to both the corresponding pure homopolymers. By combining the Polymer Reference Interaction Site Model (PRISM) integral equation theory and computational chemistry input, a predictive understanding of this phenomenon for fullerenes in RCP melts has been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…It was rationalized that the protonated porphyrin-fullerene complex is stabilized by p-p interactions. In another manifestation of electron donor-acceptor interactions, Teh, S-L. et al 39 have demonstrated the dispersion of C 60 in a polymer matrix, Fig. 2(c).…”
Section: A Non-covalent Functionalization Of Fullerenesmentioning
confidence: 96%
“…The way in which additive incorporation affects T g can afford insight into intermolecular interactions between the additive and polymer. Increase in T g resulting from additive incorporation indicates increased intermolecular interactions that limit polymer mobility [36]. Unmodified Tecoflex exhibits a glass transition that spans a broad temperature range.…”
Section: Additive-polymer Compatibilitymentioning
confidence: 99%